Congenital Hemihyperplasia with Hemipigmentation: An Anaesthesiologist’s Conundrum - Arora , Vishal; Choubey , Sanjay; Saikia , Mridusmita; Fotedar , Shivani (Research Highlights in Disease and Health Research Vol. 8, 2023)
This chapter aims to present an extremely rare case of a syndromic child with fusion of complex congenital deformities, namely congenital hemifacial hyperplasia, intense hemipigmentation and limb hemihyperplasia with leg-length discrepancy (LLD) and to supplement existing clinical knowledge. Hemihyperplasia is a heterogenous group of disorders characterized by asymmetric limb growth. Diagnosis of such syndromes may be of help in genetic counseling.